(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2020)
DETA CONFERENCE 2009 PROCEEDINGS Foreword The Distance Education and Teachers’ Training in Africa (DETA) Conference is a biennial conference that was initiated to provide a platform for educationists in Africa to meet and deliberate on educational issues in Africa. Since its inception, it has enabled educationists to exchange knowledge and enhance their capacity to engage with opportunities and challenges in education on the continent. DETA’s major objectives are to contribute to the debate on teacher training in Africa and to build capacity for the delivery of teacher training programmes in Africa. These objectives represent ways in which the conference can support NEPAD, various protocols on education and training in Africa, the Millennium Development Goals, and some of the recommendations of the All-Africa Education Ministers’ Conference on Open Learning and Distance Education. The conferences are co-hosted by the organisers and other educational institutions and organisations. The 3rd conference, co-hosted by the University of Pretoria, the University of Cape Coast, Ghana, and the University of Education, Winneba, Ghana, was held at the University of Cape Coast, Ghana, from 3 to 6 August 2009. The theme was "Issues and challenges in education in Africa – The need for a ‘new’ teacher". Subthemes included the following: - Distance education in teacher education - Teacher education, and curriculum studies and development - Special needs education and education management, law and policies, and technology in education in Africa - Mathematics and science education, language and literacy education, religious and moral education, and HIV and AIDS education More than 200 delegates from 14 African countries (Botswana, the DRC, Ghana, Kenya, Lesotho, Malawi, Mozambique, Nigeria, South Africa, Sudan, Tanzania, Uganda, Zambia and Zimbabwe) and three other countries (Canada, the UK and the USA) attended the conference. Fifty papers were read.